Anticorrosion activities of polymethacrylic acid and grafted/modified polymethacrylic acid on pure aluminium in acid medium. (2021) - Devakumar, J.; Jaya Santhi, R.; Amaladass, P.; Ramesh, V.
Highlights: The anti-corrosion studies of PMAA and grafted PMAA like PMAA/CAT, PMAA/HQ and PMAA/CAT-HQ were carried out on aluminum in 0.7 M HCl and the inhibition efficiencies were found to be 62%, 82%, 86% and 88% by potentio-dynamic polarizati The inhibition efficiency of PMAA and grafted PMAA studied by weight loss methods are in good agreement with the results obtained in potentio-dynamic polarization and electrochemical impedance spectroscopic method. The thermodynamic parameters like standard free energy and equilibrium constant were calculated from the Langmuir curves. Abstract: Polymethacrylic acid (PMAA) and modified Polymethacrylic acid functionalized with catechol (PMAA/CAT), hydroquinone (PMAA/HQ) and catechol-hydroquinone (PMAA/CAT-HQ) were synthesized by oxidative decarboxylation method using ammonium persulphate as an oxidant and characterized using UV–Visible spectroscopy, FT-IR, XRD, TGA and SEM studies. The percentage of substitution was found to be 81%, 84% and 87% respectively for PMAA/CAT, PMAA/HQ and PMAA/CAT-HQ. The anticorrosion behavior of the synthesized polymers on pure aluminium in 0.7 M HCl was studied by potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS) and weight loss (WL) methods. As the concentration of the inhibitor increases, the anticorrosion activities increases and reaches the optimum, on further increase in the inhibitor concentration, the anticorrosion activity decreased and remained constant that determines the optimum inhibition efficiency. The increase in the anticorrosion activities at the optimum inhibitor concentration of 300 ppm is found to be in the order: PMAA < PMAA/CAT < PMAA/HQ < PMAACAT-HQ and this may be due to an increase in the substitution. The PDP study indicates that the synthesized polymers act as good cathodic inhibitors on aluminium in 0.7 M HCl. EIS and WL methods have the same trend of inhibitive effect as that of PDP studies which also indicates the formation of a protective layer of polymers on the surface of the pure aluminium. The thermodynamic adsorption parameters like Kads and ΔGads were calculated using Langmuir adsorption isotherm.